Manajemen Lembaga Pengurus Asrama Ma’had Al-Jami’ah (LA_PASMA) dalam Pengelolaan Asrama di UIN Sultan Thaha Saifuddin Jambi - Toha Aliyudin; Jamaluddin Jamaluddin; Sumirah Sumirah (JMiE (Journal of Management in Education), 2023)
This study aims to analyze the management of the Dormitory Management Institution (LA_PASMA) at Ma’had Al-Jami’ah, State Islamic University Sultan Thaha Saifuddin Jambi, as a strategic instrument for character building and foreign language competency enhancement among students. The research employs a qualitative descriptive approach with data collection techniques including observation, documentation, and interviews. Data analysis follows Miles and Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that LA_PASMA management encompasses key components such as recruitment procedures, governance criteria, legality, organizational structure, and program implementation mechanisms. This management model contributes to producing graduates with integrity, competence, and global competitiveness. The study provides theoretical implications for Islamic education management literature and practical implications for dormitory administration in higher education institutions.